Pandangan Gereja Kristen tentang Penggunaan Alat Kontrasepsi: Telaah Teologis dalam Konteks Globalisasi - Tjoa Novia Yedija Setiawan; Wahyu Wijiati (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study explores the use of contraception from a Christian perspective, focusing on the Christian Church's views on issues of sexuality and reproduction. Globalization has brought about significant cultural changes, including in how society views sexual relations, family planning, and reproductive responsibility. These changes have influenced the Christian community, giving rise to diverse theological and ethical responses regarding the use of contraception. Within the Christian Church itself, there are fundamental differences of opinion. Most schools reject the use of contraception, citing specific interpretations of biblical passages that emphasize openness to life and God's will. Meanwhile, other schools view contraception as a more complex issue, requiring contextual consideration, taking into account aspects of health, family well-being, and the moral responsibility of married couples. These differing views demonstrate the theological and social dynamics that influence the Church's stance on contraception. Therefore, this study aims to provide a deeper understanding of the decision-making process regarding contraception use within the Christian community.